Idāratu Tanfīżi Barnāmaji Ta’līmi al-Lughah al-`Arabiyyah fi Markazi al-Lughah al-`Arabiyyah bi Puncak Darussalam Madura: Management of the Implementation of the Arabic Language Learning Program at Markaz Lughah Arabiyah Puncak Darussalam Madura - Fithtriyah, Aidah; Rosyada, Amrina; Hadziq, Muhammad Fadhil; Mubarok, Khusnul; Hilmi, Danial; Rasuliy, Mohammad Walid (University of Darussalam Gontor, 2024)
This study aims to determine the management of the implementation of the Arabic language learning program at Markaz Lughah Arabiyah Puncak Darussalam Madura and also to find out the problems faced in the implementation of the program. This research uses descriptive qualitative method. Data collection through observation techniques, semi-structured interviews and documentation. While analyzing the data through the analysis theory of Miles, Huberman, and Saldana which consists of data condensation, data presentation and conclusion drawing. The results showed that the management of the implementation of the Arabic language learning program at Markaz Lughah Arabiyah Puncak Darussalam Madura went well, seen from the activities of the students were very enthusiastic in participating in the program, namely the students could follow the activities until the specified time limit. In order to maximize language learning, Arabic is used as a daily communication tool. The problems faced by the markaz are the lack of teaching staff, limited facilities and learning resources, and limited learning time which affects the effectiveness of the learning process. Despite the shortcomings, the learning program held by the markaz can still run smoothly and well, where within the specified time (two semesters / one year), the students have been able to master Arabic well.